Click to Chat

1800-2000-838

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
```        If the pth,qth and rth terms of a G.P are a,b,c resp.Pove that:-
(a^(q-r))(b^(r-p))(c^(p-q))=1```
7 years ago

85 Points
```										Dear Aparna,
given,
a  = xyp-1  ,  b = xyq-1 and c = xyr-1   here,  x is first term and y is common ratio
as, G2 = AH we ahve,
b2=ac
xyq-1
aq-r = xq-r * y(p-1)(q-r)
br-p  = xr-p * y(q-1)(r-p)
cp-q = xp-q * y(p-q)(r-1)
multiply all 3 of them, we get RHS,
x0 * y0 = 1
henc proved.

All the best.
Win exciting gifts by answering the questions on Discussion Forum. So help discuss any  query on askiitians forum and become an Elite Expert League askiitian.

Anil Pannikar
IIT Bombay

```
7 years ago
Aniket Patra
48 Points
```										Just multiply the terms..and find the pth,qth and rth term by using the formula.(take x as the first term)..And then put the values in the expression..u will get (abc)^0 i.e. 1.
```
7 years ago
Think You Can Provide A Better Answer ?

## Other Related Questions on Algebra

View all Questions »
• Complete JEE Main/Advanced Course and Test Series
• OFFERED PRICE: Rs. 15,900
• View Details
Get extra Rs. 1,272 off
USE CODE: Neerajwin
Get extra Rs. 187 off
USE CODE: Neerajwin